Rwanda High Iron Bean (HIB) Impact Assessment Survey - HarvestPlus; Birachi, Eliud Abucheli; Katungi, Enid Mbabazi (International Food Policy Research Institute, 2021)
An impact assessment (IA) study was conducted in Rwanda in 2015 to determine the adoption and diffusion rates of high iron beans (HIB) varieties after eight seasons of active dissemination; understand HIB adoption and diffusion patterns across varieties and over time (the percentage of farmers currently planting, the percentage rate of addition, the percentage rate of dropout, the percentage of bean area currently under HIB, and so forth); and assess the socioeconomic and nutrition impacts resulting from HIB adoption. A nationally representative listing exercise preceded the main household survey for the impact assessment. The listing exercise was conducted across 120 rural villages in 29 provinces of Rwanda and was administered to a total of 19,575 households. The data included here are from both the listing exercise and the main impact assessment survey.